Grêmios estudantis e o movimento dos secundaristas: um estudo de casos nas escolas santistas - Ferreira, Márcia Regina (2021)
The interest in understanding the practices of a students’ fraternity in schools of São Paulo State, more specifically in the city of Santos from 1980 to 2018 is the aim presented in this essay. Besides recognizing the forms of organization of the Students’ Movement of high school sophomore students in that same period as well as the policies developed by the São Paulo State to help these fraternities in each school unit. To make it possible, a documentary has been carried out as a research that includes several studies and analyzes of these documents about fraternities, or “Student Guilds”. The essay also included conversations with ex-students who were part of these fraternities, three of them participated in the movement of Public Schools Occupation in São Paulo State. The trajectory chosen to understand the object required the study of the educational management model adopted by the São Paulo School System from the 1990s onwards, as well as a survey about the school reorganization promoted in 1995 and the analysis of the 2015 reorganization proposal. First, it has been noticed that the São Paulo government adopts an authoritarian stance without spaces for the school community to manifest themselves and be part of the school management. It was also found that after the pressures exerted by high school sophomore students in 2015, the Government was forced to dialogue with students and the community. It has also been showed the attempts of the São Paulo State to protect the student union does not reduce its importance in the school environment, but discourages students from participating, due to the extensive agenda that the Department of Education imposes. The work had as theoretical support Adrião (2020), Gadotti (2001), Ghanem (1989), Gohn (2017), (2001), Marque e Cintra (2009) and Paro (2016)